Immune regulation of canine tumour and macrophage PD‐L1 expression. (4th February 2016) - Hartley, G.; Faulhaber, E.; Caldwell, A.; Coy, J.; Kurihara, J.; Guth, A.; Regan, D.; Dow, S.
Abstract: Expression of programmed cell death receptor ligand 1 (PD‐L1) on tumor cells has been associated with immune escape in human and murine cancers, but little is known regarding the immune regulation of PD‐L1 expression by tumor cells and tumor‐infiltrating macrophages in dogs. Therefore, 14 canine tumor cell lines, as well as primary cultures of canine monocytes and macrophages, were evaluated for constitutive PD‐L1 expression and for responsiveness to immune stimuli. We found that PD‐L1 was expressed constitutively on all canine tumor cell lines evaluated, although the levels of basal expression were very variable. Significant upregulation of PD‐L1 expression by all tumor cell lines was observed following IFN‐ γ exposure and by exposure to a TLR3 ligand. Canine monocytes and monocyte‐derived macrophages did not express PD‐L1 constitutively, but did significantly upregulate expression following treatment with IFN‐ γ . These findings suggest that most canine tumors express PD‐L1 constitutively and that both innate and adaptive immune stimuli can further upregulate PD‐L1 expression. Therefore the upregulation of PD‐L1 expression by tumor cells and by tumor‐infiltrating macrophages in response to cytokines such as IFN‐ γ may represent an important mechanism of tumor‐mediated T‐cell suppression in dogs as well as in humans.